2020
DOI: 10.1039/d0sc04246c
|View full text |Cite
|
Sign up to set email alerts
|

Reversible guest-induced gate-opening with multiplex spin crossover responses in two-dimensional Hofmann clathrates

Abstract: Spin crossover (SCO) compounds are a very attractive type of switchable materials due to their potential application in molecular devices. Rational chemical tailoring of these switchable compounds is key for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 53 publications
0
44
0
Order By: Relevance
“…9 K ( T c1 ↓ = 196 K, T c1 ↑ = 205 K) and 15 K ( T c2 ↓ = 166 K, T c2 ↑ = 181 K). Such a hysteretic spin transition is usually caused by strong cooperative interactions among the magnetic centers 41 , 42 . The shifts in the Fe−N bond lengths confirm the spin transition of Fe II ions in 1 ·9/2H 2 O.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 K ( T c1 ↓ = 196 K, T c1 ↑ = 205 K) and 15 K ( T c2 ↓ = 166 K, T c2 ↑ = 181 K). Such a hysteretic spin transition is usually caused by strong cooperative interactions among the magnetic centers 41 , 42 . The shifts in the Fe−N bond lengths confirm the spin transition of Fe II ions in 1 ·9/2H 2 O.…”
Section: Resultsmentioning
confidence: 99%
“…A CO 2 -induced paramagnetic–to–ferrimagnetic variation was recently demonstrated in a porous compound, [{Ru 2 (F 3 PhCO 2 ) 4 } 2 TCNQ(OEt) 2 ]·3DCM (TCNQ(OEt) 2 = 2,5-diethoxy-7,7,8,8-tetracyanoquinodimethane; F 3 PhCO 2− = 2,4,6-trifluorobenzoate; DCM = dichloromethane), as a result of electron transfer and a structural transition involved in the adsorption of CO 2 molecules 37 . In addition to radical molecules, the spin-crossover (SCO) compounds of 3 d 4 −3 d 7 metal ions, whose spin states can be interconverted between high-spin (HS) and low-spin (LS) states in response to external stimuli, are also susceptible to the structural changes in the coordination geometry of metal centers 38 41 . Therefore, the intercorrelation between the guests and SCO frameworks potentially leads to intriguing magnetic switching that directly entangles the structural transformations involved in guest adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) Hofmann-type Fe II coordination polymers with general formula {Fe II (L ax ) 2 [M II (CN) 4 ]} represent an important source of SCO compounds, where M II = Pt II , Pd II , or Ni II and L ax is a terminal monotopic axial ligand based on pyridine/pyridine-like , and triazole rings . The Fe II ions are equatorially connected through square-planar [M II (CN) 4 ] 2– anionic metalloligands affording robust infinite [Fe II [M II (CN) 4 ] ∞ layers that are the origin of the cooperativity typically exhibited by these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Real et al reported the construction of isoreticular 2D Hofmann-type MOF Fe(5-NH 2 pym) 2 [M(CN) 4 ] (M = Pt or Pd) with 5-aminopyrimidine (5-NH 2 pym) as ligands, in which the amine groups and aromatic nitrogen atoms served as hydrogen bonding donors and acceptors, enabling enough pore space for the accommodation of guest molecules. [40] The as-synthesized phase with water as guest molecules can be dehydrated and reversibly adsorb/desorb protic solvent molecules, such as water, methanol, and ethanol, as evidenced by single-crystal diffraction studies. The vapor sorption isotherms of the bulk material showed gate-opening effect for both compounds upon these solvent vapors, demonstrating the structural transformation that is not observed in the bulk prototypical Fe(py) 2 [M(CN) 4 ] and its derivatives.…”
Section: Guest-induced Gate-opening Effectmentioning
confidence: 99%